Probiotics to reduce antibiotic administration in care home residents aged 65 years and older: the PRINCESS RCT - Butler, CC; Owen-Jones, E; Lau, M; Gillespie, D; Lown, M; Calder, PC; Stanton, H; Wootton, M; Castro Herrera, V; Bayer, A; Davies, J; Edwards, A; et al. (National Institute for Health Research, 2021)
Background Care homes are an increasingly important sector of care. Care home residents are particularly vulnerable to infections and are often prescribed antibiotics, driving antibiotic resistance. Probiotics may be a cheap and safe way to reduce antibiotic use. Efficacy and possible mechanisms of action are yet to be rigorously evaluated in this group. Objective The objective was to evaluate efficacy and explore mechanisms of action of a daily oral probiotic combination in reducing antibiotic use and infections in care home residents. Design This was a multicentre, parallel, individually randomised, placebo-controlled, double-blind trial, with qualitative evaluation and mechanistic studies. Setting A total of 310 care home residents were randomised from 23 UK care homes (from December 2016 to May 2018). Participants The participants were care home residents aged ≥ 65 years who were willing and able to give informed consent or, if they lacked capacity to consent, had a consultee to advise about participation on their behalf. Intervention A daily capsule containing an oral probiotic combination of Lactobacillus rhamnosus GG and Bifidobacterium animalis subsp. lactis BB-12 (n = 155) or matched placebo (n = 155) for up to 1 year. Main outcome measures The primary outcome was cumulative systemic antibiotic administration days for all-cause infections. Secondary outcomes included incidence and duration of infections, antibiotic-associated diarrhoea, quality of life, hospitalisations and the detection of resistant Enterobacterales cultured from stool samples (not exclusively). Methods Participants were randomised (1 : 1) to receive capsules containing probiotic or matched placebo. Minimisation was implemented for recruiting care home and care home resident sex. Care home residents were followed up for 12 months with a review by a research nurse at 3 months and at 6–12 months post randomisation. Care home residents, consultees, care home staff and all members of the trial team, including assessors and statisticians, were blinded to group allocation. Results Care home residents who were randomised to probiotic had a mean 12.9 cumulative systemic antibiotic administration days (standard error 1.49 days) (n = 152) and care home residents randomised to placebo had a mean 12.0 cumulative systemic antibiotic administration days (standard error 1.50 days) (n = 153) (adjusted incidence rate ratio = 1.13, 95% confidence interval 0.79 to 1.63; p = 0.495). There was no evidence of any beneficial effects on incidence and duration of infections, antibiotic-associated diarrhoea, quality of life, hospitalisations, the detection of resistant Enterobacterales cultured from stool samples or other secondary outcomes. There was no evidence that this probiotic combination improved blood immune cell numbers, subtypes or responses to seasonal influenza vaccination. Conclusions Care home residents did not benefit from daily consumption of a combination of the probiotics Lactobacillus rhamnosus GG and Bifidobacterium animalis subsp. lactis BB-12 to reduce antibiotic consumption. Limitations Limitations included the following: truncated follow-up of some participants; higher than expected probiotics in stool samples at baseline; fewer events than expected meant that study power may have been lower than anticipated; standard infection-related definitions were not used; and findings are not necessarily generalisable because effects may be strain specific and could vary according to patient population. Future work Future work could involve further rigorous efficacy, mechanisms and effectiveness trials of other probiotics in other population groups and settings regarding antibiotic use and susceptibility to and recovery from infections, in which potential harms should be carefully studied. Trial registration Current Controlled Trials ISRCTN16392920.